The Mediating Role of Emotional Intelligence on the Relationship between Organizational Culture and Job Performance of Accounting Staff in Yazd, Iran - Zohreh Arefmansh; Habib Ansari Samani; Fatemeh Zare Bidaki; Masoumeh Sadat Mousavi (Journal of Social Behavior and Community Health)
Background: Manpower is one of the most important resources for an organization to achieve its gsoals. Therefore, organizations are looking for appropriate plans to attract and retain efficient human resources. This study investigated the effect of the organizational culture of the accounting staff of executive bodies of Yazd province on job performance with the mediating role of emotional intelligence. Methods: This study used a correlational design with path analysis. Standard questionnaires by Queen, Scatter, and Schering were used (organizational culture, job performance, and emotional intelligence). To do so, 173 questionnaires were analyzed using the convenience sampling method. In data analysis, structural equation modeling, AMOS, and SPSS were used. Results: The results showed that organizational culture as an independent variable has a direct and significant effect on emotional intelligence as a dependent variable with a coefficient of 0.66 (P=0.000). Emotional intelligence as an independent variable has a direct effect on job performance as a dependent variable with a coefficient of 0.19 (P=0.000). Also, organizational culture as an independent variable exerts a direct effect on job performance as a dependent variable with a coefficient of 0.68 (P=0.001); indirectly, emotional intelligence is considered as a mediator with a coefficient of 0.129 (P=0.000) with a total effect of 0.81. Conclusion: Considering the positive and significant effect of organizational culture and emotional intelligence on the job performance of accounting staff and also the positive and significant effect of organizational culture on emotional intelligence, the training of all indicators of emotional intelligence is recommended to develop and increase the personal and professional abilities of individuals. Also, it is very important to study each of the indicators of organizational culture in the executive apparatus to maintain and strengthen the useful and effective factors in it and to change and correct undesirable values.